Associations Among Depression, Hemoglobin A1c Level, and Prognosis in Patients With Coronary Artery Disease: A Prospective Study - Li, Weiya; Yin, Han; Liu, Quanjun; Chen, Yilin; Liang, Yanting; Zhou, Haofeng; Ma, Huan; Geng, Qingshan (Frontiers in Psychiatry, 2022)
Background: Depression is ubiquitous in patients with coronary artery disease (CAD). The relationship between depression and hemoglobin A1c (HbA1c) is controversial. The combined effect of high HbA1c and depression on prognosis is unclear, especially in non-diabetic CAD patients. We sought to explore these associations. Methods: 558 CAD patients were included in this prospective study. Patients were grouped by HbA1c levels and the status of clinical depression. The average follow-up period was about 2.2 years, and Cox proportional hazards models were used to compare the differences of prognosis in all the groups. Results: Clinical depression had no associations with HbA1c in all CAD patients (P for Pearson correlation=0.74). In the all four groups, compared to group 1 (patients without clinical depression and low HbA1c), group 3 (without clinical depression and high HbA1c) had a higher risk of MACE (adjusted hazard ratio [aHR],1.97; 95% confidence interval [CI], 1.2-3.25) and composite events (aHR,1.67; 95% CI, 1.09-2.53). Group 4 (patients with clinical depression and high HbA1c) had higher HRs for MACE (aHR, 2.9; 95%CI, 1.32-6.38) and composite events (aHR,2.12; 95% CI, 1.06-4.25). In CAD patients without diabetes, patients with clinical depression and high HbA1c had a higher risk of MACE (HR,2.71; 95% CI, 1.02-7.19), noncardiac readmission (HR,3.48; 95% CI, 1.26-9.57) and composite events (HR,2.44; 95% CI, 1.08-5.53) than those with no clinical depression and low HbA1c. In patients with comorbidities of depression and diabetes, patients with depression and high HbA1c more likely to experienced noncardiac readmissions (HR,4.49; 95% CI, 1.31-15.38) than patients with no depression and low HbA1c only. In all the above analysis, p values for interaction between clinical depression and HbA1c were not statistically significant. Conclusions: The presence of both depression and high HbA1c lead to a worse prognosis in CAD patients than one risk factor alone, no matter with or without the comorbidity of diabetes in these CAD patients. For patients with CAD and depression, lower HbA1c may be required.